A preparation method and application of a high-nickel polycrystalline ternary precursor

Through the multi-step seed preparation process, the problem of poor particle uniformity in the synthesis of high nickel large particle precursors is solved, and the preparation of high nickel large particle precursors with high specific capacity and cyclic performance is achieved, with good rate performance.

CN119145049BActive Publication Date: 2025-03-21JIANGXI JIANA ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411661707.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-21
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the process of synthesis of high-nickel large-particle precursors, there are problems of cracking, particle bonding, twinning and poor particle uniformity, which affects the performance of material properties.

Method used

A multi-step seed preparation process ("grain source-seed-growth" three-stage reaction) is adopted to achieve step-by-step and hierarchical growth of particles by controlling the reaction temperature and pH value, and a high-nickel large-particle precursor with high specific capacity and cyclic performance is obtained.

Benefits of technology

A high-nickel large-particle precursor with large particle size and good particle consistency is achieved, with a high peak-strength ratio, which can quickly pass through lithium ions and exhibit good rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145049B_ABST
    Figure CN119145049B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-nickel polycrystalline ternary precursor. The method can realize the step-by-step and hierarchical growth of particle size by adopting a multi-step seed preparation process, showing characteristics similar to a core-shell structure. At the same time, the first two stages of the process are controlled at medium and low temperatures, and the temperature of the last stage of growth is maintained at a high temperature, so that a precursor with good particle dispersion, uniform primary particles, obvious internal radial structure and clear layered contours can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy lithium battery positive electrode materials, and mainly relates to the preparation of a high-nickel large-particle nickel-cobalt-manganese hydroxide, which is used for sintering lithium battery positive electrode materials. As a key core material of the positive electrode material, it improves the capacity and cycle performance of the battery and is applied in the field of new energy power vehicles. Background Art

[0002] With the development of new energy vehicles, the automotive industry has put forward higher requirements and specifications for the capacity, cycle, safety and other aspects of lithium-ion batteries. Coupled with the strict policies on fuel vehicles and the accelerated delisting process, new energy vehicles have higher and higher requirements for endurance and safety performance. At present, the main development directions at home and abroad are medium-nickel high-voltage, high-nickel, and solid-state batteries. The high-nickel direction has always been a research focus and the first choice for the application of endurance in high-end power vehicles.

[0003] High-nickel large-particle products generally have a high degree of sphericity, a rounded particle surface, short primary particles, and a certain radial structure, which is conducive to the full reaction with lithium salts during the sintering process, and is conducive to the rapid passage of lithium ions, and can also reduce the occurrence of side reactions with the interface. In addition, the lithium transfer kinetics of large-particle NCM particles are much better than those of single-crystal products at voltages above high voltage (3.80V), which is also an advantage of polycrystalline materials. At the same time, the larger secondary particles of multi-crystalline NCM exhibit high overpotentials and higher specific capacity and rate performance. Therefore, high-nickel multi-crystalline materials are currently a mainstream product in the market and an indispensable development trend. However, in the process of synthesizing high-nickel large-particle precursors, problems such as cracking, particle bonding (twinning), and poor particle uniformity are often accompanied, which in turn affect the performance of the material. Summary of the invention

[0004] The purpose of the present invention is to prepare a kind of particle with large particle size, good particle consistency, porous and loose interior, clear outline, and clear radial structure with high peak intensity ratio (I 101 / I 001 >1.0). This material has high specific capacity and cycle performance, and can achieve rapid passage of lithium ions, showing good rate performance.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention comprises the following steps:

[0006] A method for preparing a high-nickel polycrystalline ternary precursor, comprising selecting soluble nickel salt, cobalt salt and manganese salt as raw materials, preparing a mixed metal salt solution according to the molar ratio of nickel, cobalt and manganese in the required nickel-cobalt-manganese hydroxide, wherein the nickel-cobalt-manganese hydroxide is composed of Ni x Co y Mn z(OH)2 indicates that the molar ratio range of nickel, cobalt, and manganese is 0.85 < x < 0.95, 0.05 < y < 0.10, 0 < z < 0.05. Sodium hydroxide solution is used as the precipitant, and ammonia water is used as the complexing agent to achieve the coprecipitation of nickel, cobalt, and manganese elements.

[0007] The specific preparation steps are as follows:

[0008] 1. Prepare a nickel-cobalt-manganese salt solution with a metal ion concentration of 1.5 - 2.5 mol / L, a sodium hydroxide solution with a concentration of 8 - 12 mol / L, and an ammonia water solution with a concentration of 7.0 - 10 mol / L.

[0009] 2. Preparation of the grain source precursor

[0010] a. Add deionized water to the sealed reactor to submerge the middle layer and stir. Pass liquid nitrogen under the liquid as a protective gas for more than 3 h, with a flow rate of 1 - 2 m 3 / h, and at the same time control the stirring speed to be 300 - 350 rpm and the reaction temperature to be 45 - 55 °C;

[0011] b. Add the complexing agent ammonia water to the reactor in sequence, control the ammonia value to be 1.0 - 3.0 g / L, and add the alkali solution to adjust the pH value of the system to 11.0 - 12.0 as the bottom liquid and starting condition of the reaction;

[0012] c. Add the nickel-cobalt-manganese salt solution, sodium hydroxide solution, and ammonia water solution to the reactor simultaneously and maintain the introduction of the inert gas. During this period, maintain the pH value of the system at 11.0 - 12.0 and the ammonia value at 1.0 - 3.0 g / L, and the reaction time is 30 - 120 min;

[0013] d. Gradually lower the pH value of the system to 10.5 - 10.9 and continue the reaction;

[0014] e. Lower the pH value of the system to 10.0 - 10.3 again and continue the reaction;

[0015] f. Until the reactor is full, stop feeding. When the particle size D50 in the reactor is 1.5 - 2.5 μm, the reaction ends, and the grain source is obtained for use as the seed in the seed stage;

[0016] g. Repeat steps a - f 1 - 2 times to obtain the grain source precursor.

[0017] 3. Preparation of the seed precursor

[0018] 1) Use the above grain source precursor as the grain source of this seed. The number of rounds of grain source precursor used is 1 - 3, and the specific usage amount is determined according to the particle size of the grain source;

[0019] 2) Add the crystal source precursor to the new reactor, add water until the liquid level reaches the middle stirring position of the reactor, and then start nitrogen replacement for >3h, with a flow rate of 2~5m 3 / h, during which ammonia water and alkali solution are added to maintain the pH value of the system at 10.0-10.3 (the pH at the end of process e in step 2), and the ammonia value at 2.0-4.0 g / L; at the same time, the stirring speed is controlled at 200-250 rpm and the reaction temperature is controlled at 45-55 °C;

[0020] 3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; when the reactor is full, it enters the concentration equipment, and the reactor and the concentrator are kept circulating during this period;

[0021] 4) When the particle size D50 in the kettle is 3.5~6.0μm, the reaction is completed and a seed crystal precursor is obtained.

[0022] 4. Preparation of large particle precursors

[0023] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 10-30g / L before starting the machine, and finally add ammonia and alkali. At the same time, control the stirring speed to 180-220rpm and the reaction temperature to 55-65℃;

[0024] (2) Control the pH value of the system to 10.0-10.6 and the ammonia value to 3.0-5.0 g / L;

[0025] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; in the early stage, feed the materials at a flow rate of 100-300 L / h until the reactor is full. When the particle size D50 in the reactor is less than 10 um, stop the reactor for material separation. Use the split reactor process to divide half of the materials into other reactors for reaction. After material separation, start the two reactors at the same time to feed materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 300-600 L / h. During this period, keep the reactor and the concentrator circulating for concentration;

[0026] (4) introducing air into the kettle according to the solid content in step (1);

[0027] (5) When the particle size D50 in the kettle is 17.5±0.50μm, the reaction is completed, the air supply is stopped, and the nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0028] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 30 to 80 g / L to obtain a ternary precursor filter cake;

[0029] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0030] (8) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0031] Furthermore, the operation of introducing air in step (3) is specifically as follows:

[0032] When the solid content is ≤20g / L and the particle size D50 in the kettle is 10μm, start to introduce air with 5% oxygen content until the machine is shut down; when the solid content is >20g / L and the particle size D50 in the kettle is 7.0μm, start to introduce air with 8% oxygen content, and when the particle size D50 in the kettle is 10μm, increase the oxygen content to 12%, and when the particle size D50 in the kettle is 15μm, stop introducing nitrogen and increase the oxygen content to 21% until the machine is shut down.

[0033] The beneficial effects of the present invention are:

[0034] (1) The present invention adopts a multi-step seed preparation process (three-stage reaction of "grain source-seed-growth") to achieve step-by-step and hierarchical growth of particle size, showing characteristics similar to core-shell structure; at the same time, the first two stages are controlled at medium and low temperatures, and the temperature of the last stage of growth is kept at high temperature, so that a precursor with good particle dispersion, uniform primary particles, obvious internal radial structure and clear layered contours can be obtained. The obtained product particles have a D50 of 17.5±0.5μm, the internal pores of the particles are evenly distributed, and they show a high peak intensity ratio (I 101 / I 001 >1.0), the material has high specific capacity and cycle performance, and can achieve rapid passage of lithium ions, showing good rate performance.

[0035] (2) Compared with the traditional clean water start-up and process separation process, the large particles prepared by the seed crystal process have a high degree of controllability and experimental repeatability, which can greatly improve the stability of the material preparation process and the consistency of the results, while also improving the sphericity and process operability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a typical internal structure analysis diagram of the high-nickel ternary precursor of the present invention.

[0037] Figure 2Schematic diagram A and physical analysis diagram B of the typical internal structure of the high-nickel ternary precursor of the present invention (from the inside to the outside in schematic diagram A are: grain-seed-growth).

[0038] Figure 3 This is the SEM image of the precursor prepared in Example 1 of the present invention.

[0039] Figure 4 This is the SEM image of the precursor prepared in Example 2 of the present invention.

[0040] Figure 5 This is the SEM image of the precursor prepared in Example 3 of the present invention.

[0041] Figure 6 This is the SEM image of the precursor prepared in Comparative Example 1 of the present invention.

[0042] Figure 7 This is the SEM image of the precursor prepared in Comparative Example 2 of the present invention.

[0043] Figure 8 This is the SEM image of the precursor prepared in Comparative Example 3 of the present invention.

[0044] Fig. 9 This is the SEM image of the precursor prepared in Comparative Example 4 of the present invention.

[0045] Fig.10 This is a comparison chart of the XRD of the precursors prepared in Examples 1 to 3 of the present invention and Comparative Example 1.

[0046] Fig.11 This is a comparison chart of the XRD of the precursor and the positive electrode prepared in Example 2 of the present invention and Comparative Example 1.

[0047] Fig.12 This is a comparison chart of the cycle performance of materials prepared in Example 2 of the present invention and Comparative Example 1.

[0048] Fig.13 This is a comparison chart of the soft package performance of materials prepared in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0049] The present invention will be further described in detail below in conjunction with the embodiments.

[0050] Example 1

[0051] 1. Prepare a nickel-cobalt-manganese salt solution with a metal ion concentration of 2.0 mol / L, the molar ratio of nickel, cobalt and manganese elements in the metal salt solution is 88.5:8:3.5, prepare a sodium hydroxide solution with a concentration of 10.80 mol / L, and prepare an ammonia solution with a concentration of 7.5 mol / L.

[0052] 2. Preparation of grain source precursor

[0053] a. Add deionized water to the sealed reactor to cover the middle layer and stir. Pass nitrogen protection gas under the liquid for more than 3 hours, with a flow rate of 2m 3 / h, while stirring at 340rpm, the temperature was controlled at 50℃.

[0054] b. Add complexing agent ammonia water to the reactor in sequence, control the ammonia value at 1.75g / L, and add alkali solution to adjust the pH value of the system to 11.60, which serves as the base liquid and starting condition for the reaction.

[0055] c. Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and maintain the inert gas flow, during which the pH value of the system is maintained at 11.6 and the ammonia value is maintained at 1.75 g / L, and the reaction is continued for 60 min;

[0056] d. Gradually reduce the system saturation, reduce the system pH value to 10.70, and continue the reaction;

[0057] e. Reduce the system saturation again, lower the system pH to 10.15, and continue the reaction;

[0058] f. Stop feeding when the reactor is full. When the particle size D50 in the reactor is 1.80 μm, the reaction is finished.

[0059] g. Repeat steps a to f 1 to 2 times to obtain a grain source precursor.

[0060] 3. Preparation of seed crystal precursor

[0061] 1) Using the above-mentioned grain source precursor as the grain source of this seed crystal, the amount used is one round of grain source precursor;

[0062] 2) Add the crystal source precursor to the new reactor, add water until the liquid level reaches the middle stirring position of the reactor, and then start nitrogen replacement for >3h, with a flow rate of 4m 3 / h, during which ammonia water and alkali solution were added to maintain the pH value of the system at 10.15 (maintaining the pH at the end of step (2)), and the ammonia value at 2.75 g / L; at the same time, the stirring speed was controlled at 220 rpm and the reaction temperature was 50°C;

[0063] 3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; when the reactor is full, it enters the concentration equipment, and the reactor and the concentrator are kept circulating during this period;

[0064] 4) When the particle size D50 in the kettle is 4.50 μm, the reaction is completed and a seed crystal precursor is obtained.

[0065] 4. Preparation of large particle precursors

[0066] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 20g / L before starting the machine, and finally add ammonia and alkali. At the same time, control the stirring speed to 200rpm and the reaction temperature to 60℃;

[0067] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0068] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; in the early stage, feed the materials at a flow rate of 200L / h until the reactor is full. When the particle size D50 in the reactor is 8.76um, stop the reactor for material division. Use the split reactor process to divide half of the materials into other reactors for reaction. After material division, start the two reactors at the same time to feed materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0069] (4) When the particle size D50 in the kettle is 10 μm, air with 5% oxygen content is introduced until the machine is shut down;

[0070] (5) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, the air supply is stopped, and the nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0071] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0072] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0073] (8) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0074] The SEM morphology of the precursor is as follows Figure 3 shown.

[0075] Example 2

[0076] Steps 1, 2, and 3 of this embodiment are the same as those of embodiment 1.

[0077] 4. Preparation of large particle precursors

[0078] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed crystal precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 25g / L before starting the machine. Finally, add ammonia and alkali, and control the stirring speed to 200rpm and the reaction temperature to 60℃;

[0079] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0080] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction. In the early stage, feed the materials at a flow rate of 200 L / h until the reactor is full. When the particle size D50 in the reactor is 8.76 um, stop the machine for material division. Use the split-pot process to divide half of the materials into other reactors for reaction. After the material division, start the two reactors at the same time to feed the materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400 L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0081] (4) When the particle size D50 in the kettle is 7.0 μm, start to introduce air with an oxygen content of 5%. When the particle size D50 in the kettle is 10 μm, increase the oxygen content to 8% until the machine is shut down.

[0082] (5) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, the air is turned off, and the nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0083] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0084] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0085] (8) Screen and demagnetize the high-nickel large-particle precursor material to obtain the corresponding precursor product. The SEM morphology of the precursor is as follows: Figure 4 shown.

[0086] Example 3

[0087] Steps 1, 2, and 3 of this embodiment are the same as those of embodiment 1.

[0088] 4. Preparation of large particle precursors

[0089] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 20g / L before starting the machine. Finally, add ammonia and alkali, and control the stirring speed to 200rpm and the reaction temperature to 60℃;

[0090] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0091] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction. In the early stage, feed the materials at a flow rate of 200 L / h until the reactor is full. When the particle size D50 in the reactor is 8.76 um, stop the machine for material division. Use the split-pot process to divide half of the materials into other reactors for reaction. After the material division, start the two reactors at the same time to feed the materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400 L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0092] (4) When the particle size D50 in the kettle reaches 7.0 μm, start to introduce air with an oxygen content of 8%. When the particle size D50 in the kettle reaches 10 μm, increase the oxygen content to 12% until the machine is shut down. When the particle size D50 in the kettle reaches 15 μm, turn off the nitrogen and increase the oxygen content to 21% until the machine is shut down.

[0093] (5) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, the air is turned off, and the particle size is re-measured after shutdown. If there is no abnormality, the slurry is placed in the aging tank for aging before washing;

[0094] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0095] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0096] (8) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0097] The SEM morphology of the precursor is as follows Figure 5 shown.

[0098] Comparative Example 1

[0099] Steps 1, 2, and 3 of this embodiment are the same as those of embodiment 1.

[0100] 4. Preparation of large particle precursors

[0101] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 20g / L before starting the machine, and finally add ammonia and alkali. At the same time, control the stirring speed to 200rpm and the reaction temperature to 70℃;

[0102] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0103] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; in the early stage, feed the materials at a flow rate of 200L / h until the reactor is full. When the particle size D50 in the reactor is 8.76um, stop the reactor for material division. Use the split reactor process to divide half of the materials into other reactors for reaction. After material division, start the two reactors at the same time to feed materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0104] (4) When the particle size D50 in the kettle is 10 μm, air with 5% oxygen content is introduced until the machine is shut down;

[0105] (5) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, the air supply is stopped, and the nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0106] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0107] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0108] (8) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0109] The SEM morphology of the precursor is as follows Figure 6 shown.

[0110] Comparative Example 2

[0111] Steps 1, 2, and 3 of this embodiment are the same as those of embodiment 1.

[0112] 4. Preparation of large particle precursors

[0113] (1) Add pure water to the reactor in advance, introduce nitrogen for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 20g / L before starting the machine, and finally add ammonia and alkali. At the same time, control the stirring speed to 180rpm and the reaction temperature to 60℃;

[0114] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0115] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; in the early stage, feed the materials at a flow rate of 200L / h until the reactor is full. When the particle size D50 in the reactor is 8.76um, stop the reactor for material division. Use the split reactor process to divide half of the materials into other reactors for reaction. After material division, start the two reactors at the same time to feed materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0116] (4) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed and nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0117] (5) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0118] (6) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0119] (7) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0120] The SEM morphology of the precursor is as follows Figure 7 shown.

[0121] Comparative Example 3

[0122] Steps 1, 2, and 3 of this embodiment are the same as those of embodiment 1.

[0123] 4. Preparation of large particle precursors

[0124] (1) Add pure water to the reactor in advance, introduce nitrogen for replacement for a period of time, then add the seed precursor to the reactor, and then add water to the middle stirring position of the reactor. Control the solid content in the reactor to 35g / L before starting the machine, and finally add ammonia and alkali. At the same time, control the stirring speed to 200rpm and the reaction temperature to 60℃;

[0125] (2) The pH value of the control system is 10.15 and the ammonia value is 3.75 g / L;

[0126] (3) Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing to start the reaction; in the early stage, feed the materials at a flow rate of 200L / h until the reactor is full. When the particle size D50 in the reactor is 8.76um, stop the reactor for material division. Use the split reactor process to divide half of the materials into other reactors for reaction. After material division, start the two reactors at the same time to feed materials until the reactors are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 400L / h. During this period, keep the reactor and the concentrator in circulation for concentration;

[0127] (4) When the particle size D50 in the kettle is 10 μm, air with 5% oxygen content is introduced until the machine is shut down;

[0128] (5) When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, the air supply is stopped, and the nitrogen is retained. After the machine is shut down and the particle size is re-measured and no abnormality is found, the slurry is placed in the aging tank for aging before washing;

[0129] (6) The slurry in the aging tank is pumped into a washing device and washed with a sodium hydroxide solution having a concentration of 40 g / L to obtain a ternary precursor filter cake;

[0130] (7) placing the ternary precursor filter cake in an oven for static drying, and when the moisture content is qualified, the drying is completed to obtain a needle-shaped, internally porous, evenly distributed, high-nickel large-particle precursor material with a high specific surface area;

[0131] (8) Screening and demagnetizing the high-nickel large-particle precursor material to obtain the corresponding precursor product.

[0132] The SEM morphology of the precursor is as follows Figure 8 shown.

[0133] Comparative Example 4

[0134] The traditional clean water start-up is used to produce large particle products.

[0135] 1. Prepare a nickel-cobalt-manganese salt solution with a metal ion concentration of 2.0 mol / L, the molar ratio of nickel, cobalt and manganese elements in the metal salt solution is 88.5:8:3.5, prepare a sodium hydroxide solution with a concentration of 10.80 mol / L, and prepare an ammonia solution with a concentration of 7.5 mol / L.

[0136] 2. Add deionized water to the sealed reactor to submerge the middle layer and stir. Pass nitrogen protection gas under the liquid for >3h, flow rate 4m 3 / h, while stirring at 200 rpm, the temperature was controlled at 60°C.

[0137] 3. Add complexing agent ammonia water to the reactor in sequence, control the ammonia value at 3.75g / L, and add alkali solution to adjust the pH value of the system to 11.60, which serves as the base liquid and starting condition for the reaction.

[0138] 4. Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and keep the inert gas flowing. During this period, the pH value of the system is maintained at 11.60 and the ammonia value is maintained at 3.75 g / L. The reaction is continued for 20 minutes.

[0139] 5. Gradually reduce the system saturation, reduce the system pH value to 10.15, and continue the reaction;

[0140] 6. The same as (4), (5), (6), (7), and (8) in the fourth step of Example 1.

[0141] The SEM morphology of the precursor is as follows Fig. 9 shown.

[0142] Experiment 1: The finished precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were observed and tested using an electron scanning microscope, and their relevant physical and chemical indicators were measured. The specific data are shown in Table 1, and the SEM images are shown in Table 1. Figures 3~9 .

[0143] Table 1 Comparison of relevant physical and chemical indicators of the precursors obtained in Examples 1 to 3 and Comparative Examples 1 to 4

[0144]

[0145] From Table 1 and Figures 3~9 It can be seen that: (1) For super-large particle products, with the intervention of later oxidation, the thickness of the primary whiskers of the particles can be improved (in Examples 1 to 3, as the oxidation increases, the whiskers become thinner in turn), thereby improving the specific surface area of ​​the particles without causing a significant change in the tap density; (2) With the increase of the solid content at startup, the reaction time is theoretically prolonged, and the amount of oxidation in the later stage should be increased simultaneously to avoid the problem of insufficient oxidation caused by the high solid content in the later stage (the feedback particle whiskers are thick and dense); (3) With the increase of temperature in the growth stage, the cracking and agglomeration phenomena can be effectively improved (as reflected by the SEM of Comparative Example 1), but the increase in temperature will cause the primary particles of high nickel products to be thicker, resulting in a lower specific surface area; (4) For the process of large particles and large specific surface area, the later oxidation process plays an important role in improving the specific surface area; (5) When using clean water to start the machine, the particle agglomeration phenomenon is serious (there are more peanut-shaped structures), and the process is accompanied by small particles, fragments and cracking problems, which is very unfavorable to the quality of the product and the repeatability of the later experiments.

[0146] Experiment 2: The precursor products prepared in Examples 1 to 3 and Comparative Example 1 were subjected to XRD analysis. The results are shown in Tables 2 and Fig.10 .

[0147] Table 2 Comparison of XRD spectra of the precursor products of Examples 1 to 3 and Comparative Example 1

[0148]

[0149] From Table 2 and Fig.10 It can be seen that the high-nickel product designed by the present invention shows a strong peak intensity ratio (I101 / I001>1.0), which can well exert the capacity density and cyclability of the material.

[0150] Experiment 3: The precursor materials prepared in Example 2 and Comparative Example 1 were sintered, and LiOH·H2O was mixed in a ratio of 1:1.05. The cathode materials were sintered in a tube furnace under an oxygen atmosphere at 450°C for 6 hours to 750°C for 15 hours. A series of characterization tests were performed. The specific test results are as follows:

[0151] 1. XRD characterization

[0152] The XRD characterization results are shown in Fig.11 ,from Fig.11 It can be seen that the XRD of the precursors of the two materials before calcination are consistent with the PDF card of nickel hydroxide, and the characteristic peaks of XRD after calcination are consistent with the characteristic peaks of LiNiO2, and the peak shape is sharp, and the 006 / 012 and 021 / 016 peak separation effects are significant, indicating that the calcined materials have a relatively intact layered structure, and 003 / 104 are 1.62 (Example 2) and 1.58 (Comparative Example 1), respectively, and the Li / Ni mixing degree of the materials is low. It shows that the structures of the two materials are basically the same.

[0153] 2. Power-off performance test

[0154] The same mass of the sintered positive electrode material was used to prepare a button half-cell with the positive electrode material, acetylene black and PVDF in a ratio of 92:4:4, and a metal lithium sheet was used as the negative electrode. The prepared button half-cell was tested for electrochemical performance under the conditions of 2.8~4.30V and 0.2C, and the results are shown in Table 3.

[0155] Table 3 Comparison of the electrical performance of Example 2 and Comparative Example 1

[0156]

[0157] It can be seen from Table 3 that the initial discharge capacity of the material in Example 2 is relatively high, which is 212 mAh g ~1 The initial efficiency is about 88.5%. The initial discharge capacity of the material in Comparative Example 1 is relatively low, at 205 mAh g ~1 Around, the initial effect is below 87%.

[0158] Then, at room temperature (25°C), the materials of Example 2 and Comparative Example 1 were subjected to 30-50 weeks of cycle performance testing at 0.5°C and 1.0°C. The results are shown in Table 1. Fig.12 .

[0159] from Fig.12 It can be seen that the cycle performance of the material in Example 2 is better than that of Comparative Example 1, and the retention rate after about 50 cycles at current densities of 0.5C and 1C is also good, which is 94~97% and above 89% respectively; while the retention rate of the material in Comparative Example 1 after about 50 cycles at current densities of 0.5C and 1C is about 92~95% and 87~88% respectively.

[0160] 3. Soft pack performance evaluation

[0161] According to the activity ratio of 90:5:5, matching graphite, making soft pack battery, controlling N / P=1, its first cycle charge and discharge curve is as follows Fig.13 shown.

Claims

1. A method for preparing a high-nickel polycrystalline ternary precursor, characterized in that: Soluble nickel salts, cobalt salts, and manganese salts are selected as raw materials, sodium hydroxide solution is used as a precipitating agent, and ammonia water is used as a complexing agent to achieve the coprecipitation of nickel, cobalt, and manganese elements, thereby obtaining a nickel-cobalt-manganese ternary material precursor. The composition of the nickel-cobalt-manganese ternary material precursor is NixCoyMnz(OH)2, and the molar ratio range of nickel, cobalt, and manganese is 0.85 < x < 0.95, 0.05 < y < 0.10, 0 < z < 0.05, including the following steps: S1: Prepare nickel-cobalt-manganese salt solution, sodium hydroxide solution, and ammonia water solution; S2: Prepare the grain source precursor; S3: Prepare the seed precursor; S4: Prepare the product large particle precursor; Among them, the specific steps for preparing the product large particle precursor in S4 are: (1) Add pure water to the reaction kettle, purge with nitrogen for a period of time, then add the seed precursor to the reaction kettle, and then add water to the middle stirring position of the kettle. Control the solid content in the kettle before starting the machine to be 10 - 30 g / L. Finally, add ammonia and alkali to control the pH value of the system to be 10.0 - 10.6 and the ammonia value to be 3.0 - 5.0 g / L. At the same time, control the stirring speed to be 180 - 220 rpm and the reaction temperature to be 55 - 65 °C; (2) Add the nickel-cobalt-manganese salt solution, sodium hydroxide solution, and ammonia water solution into the reaction kettle simultaneously and maintain the introduction of inert gas to start the reaction; in the early stage, feed at a flow rate of 100 - 300 L / h until the reaction kettle is full. When the particle size D50 in the kettle is less than 10 um, stop the machine for material separation. Adopt the process of separating the kettle, divide half of the material out to other kettles for reaction, and then start the two kettles to feed simultaneously until they are full again, and then enter the concentration equipment. At the same time, increase the metal liquid flow rate to 300 - 600 L / h. During this period, keep the kettle and the concentrator circulating for concentration; (3) Introduce air into the kettle according to the solid content in step (1); (4) When the particle size D50 in the kettle is 17.5 ± 0.50 μm, the reaction ends, stop introducing air, retain nitrogen. After复测 the particle size without abnormality after stopping the machine, discharge the slurry to the aging tank for aging, waiting for washing; (5) Pump the slurry in the aging tank into the washing equipment and wash it with sodium hydroxide solution with a concentration of 30 - 80 g / L to obtain a ternary precursor filter cake; (6) Place the ternary precursor filter cake in an oven for static drying. When the moisture is qualified, the drying ends, and the high-nickel large particle precursor material is obtained; (7) Screen and demagnetize the high-nickel large particle precursor material to obtain the corresponding precursor finished product; The specific operation of introducing air in step (3) is as follows: when the solid content is 20 g / L and the particle size D50 in the kettle is 10 μm, air with an oxygen content of 5% is introduced until the machine is shut down. When the particle size D50 in the kettle is 17.50 μm, the reaction is completed, and the introduction of air is stopped, while nitrogen is retained; or when the solid content is 20 g / L and the particle size D50 in the kettle is 7.0 μm, air with an oxygen content of 8% is introduced. When the particle size D50 in the kettle is 10 μm, the oxygen content is increased to 12% until the machine is shut down. When the particle size D50 in the kettle is 15μm, turn off the nitrogen, increase the oxygen content to 21% until the machine is shut down, when the particle size D50 in the kettle is 17.50μm, the reaction is over and the air is turned off; or when the solid content is 25g / L and the particle size D50 in the kettle is 7.0μm, start to introduce air with 5% oxygen content, when the particle size D50 in the kettle is 10μm, increase the oxygen content to 8% until the machine is shut down; when the particle size D50 in the kettle is 17.50μm, the reaction is over, turn off the air and keep the nitrogen.

2. The method for preparing a high-nickel polycrystalline ternary precursor according to claim 1, characterized in that: The molar concentration of the nickel-cobalt-manganese salt solution in S1 is 1.5-2.5 mol / L, the molar concentration of the sodium hydroxide solution is 8-12 mol / L, and the molar concentration of the ammonia water is 7.0-10 mol / L.

3. The method for preparing a high-nickel polycrystalline ternary precursor according to claim 1, characterized in that: The specific steps of preparing the grain source precursor in S2 are: a. Add deionized water to the sealed reactor to submerge the middle layer and stir, and introduce nitrogen protection gas under the liquid for more than 3 hours, with a flow rate of 1-2m 3 / h, while stirring at 300-350rpm, the temperature is controlled at 45-55℃; b. Add complexing agent ammonia and alkali solution to the reactor in sequence, control the ammonia value to 1.0-3.0 g / L, and the system pH value to 11.0-12.0, as the base liquid and starting conditions for the reaction; c. Add nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor simultaneously and maintain the inert gas flow, during which the pH value of the system is maintained at 11.0 to 12.0, the ammonia value is maintained at 1.0 to 3.0 g / L, and the reaction time is 30 to 120 min; d. Gradually reduce the system temperature to 10.5-10.9 and continue the reaction; e. Reduce the system to 10.0-10.3 again and continue the reaction; f. Stop feeding when the reactor is full. When the particle size D50 in the reactor is 1.5-2.5 μm, the reaction is over. g. Repeat steps a to f 1 to 2 times to obtain a grain source precursor.

4. The method for preparing a high-nickel polycrystalline ternary precursor according to claim 1, characterized in that: The specific steps of preparing the seed crystal precursor in S3 are: 1) Add the crystal source precursor to a new reactor, add water until the liquid level reaches the middle stirring position of the reactor, and then start nitrogen replacement for >3h, with a flow rate of 2~5m 3 / h, during which ammonia water and alkali solution are added to maintain the pH value of the system at 10.0-10.3 and the ammonia value at 2.0-4.0 g / L; at the same time, the stirring speed is controlled at 200-250 rpm and the reaction temperature is controlled at 45-55°C; 2) Adding nickel-cobalt-manganese salt solution, sodium hydroxide solution and ammonia solution into the reactor at the same time and maintaining the inert gas flow to start the reaction; when the reactor is full, it enters the concentration equipment, and the reactor and the concentrator are kept in circulation; 3) When the particle size D50 in the kettle is 3.5-6.0 μm, the reaction is completed and a seed crystal precursor is obtained.

5. The method for preparing a high-nickel polycrystalline ternary precursor according to claim 4, characterized in that: The grain source precursor used in S3 is the grain source precursor prepared in 1 to 3 rounds of S2.

Citation Information

Patent Citations

  • Positive electrode material precursor and preparation method thereof, positive electrode material, lithium ion battery and electric equipment

    CN117430170A

  • Positive electrode material precursor, positive electrode material and application

    CN118108267A

  • Preparation method of ultra-small particle precursor with high sphericity degree

    CN118978189A